Pathological autopsy of a patient that underwent a successful ablation of an electrical storm from the left ventricular summit - Hori, Yuichi; Nakahara, Shiro; Mine, Sohtaro; Anjo, Naofumi; Fujii, Akiko; Ueda, Yoshihiko; Taguchi, Isao (Heart and vessels, 2016)
A 65-year-old man with non-ischemic cardiomyopathy, underwent an autopsy 2 months after the successful ablation of a sustained left ventricular (LV) summit ventricular tachycardia (VT). The patient died due to interstitial pneumonia from amiodarone use. The earliest activation sites of the VT were documented from both inside the anterior interventricular vein (AIV) and epicardial surface. The diameter of the AIV was 3–4 mm, and the radiofrequency (RF) lesion inside the AIV was a slight lesion due to high impedance with a high temperature. The lesion from the epicardial surface was also superficial and insufficient due to neighboring coronary arteries and the existence of epicardial fat. A successful application was performed from the LV endocardium, and diffuse myocardial fibrosis was observed in the mid-myocardium including inside the RF lesions. The actual relationship between the myocardial fibrosis and LV summit VT remains unclear, but this case showed the difficulty of achieving a successful ablation from the epicardial side, when the focus exists in the mid-myocardium around the LV summit.